Ribonucleosides for an Artificially Expanded Genetic Information System - Kim, Hyo-Joong (American Chemical Society, 2014)
[Image: see text] Rearranging hydrogen bonding groups adds nucleobases to an artificially expanded genetic information system (AEGIS), pairing orthogonally to standard nucleotides. We report here a large-scale synthesis of the AEGIS nucleotide carrying 2-amino-3-nitropyridin-6-one (trivially Z) via Heck coupling and a hydroboration/oxidation sequence. RiboZ is more stable against epimerization than its 2′-deoxyribo analogue. Further, T7 RNA polymerase incorporates ZTP opposite its Watson–Crick complement, imidazo[1,2-a]-1,3,5-triazin-4(8H)one (trivially P), laying grounds for using this “second-generation” AEGIS Z:P pair to add amino acids encoded by mRNA.